A comprehensive review on solar tricycles. (2020) - Devan, P.K.; Bibin, Chidambaranathan; Krrishana, Anumala Gautam; Ashwin, M.; Bala Kumar, K.; Dinesh, K.B.
Abstract: A tricycle is a three-wheeled human-powered vehicle. This vehicle is powered by humans so greater human effort is required for operating this vehicle. Tricycles are classified as a hand-driven tricycle, motorized tricycle, electric tricycle. The hand-driven tricycle makes the user tiring. The motorized tricycle uses internal combustion engine which may lead to pollute the environment. The main objective of this work is to produce an eco-friendly motorized tricycle. This electric tricycle uses a motor which is driven by energy stored in the battery. The energy can be obtained from non-conventional sources thereby causing no harm to the environment. In this work, photovoltaic cells were used to obtain the electricity needed to drive the motor. These photovoltaic cells convert solar energy into electric energy. Therefore, this eco-friendly method is used for producing electricity. The main aim of this work is to study a tricycle powered by energy obtained by solar cells for physically challenged people. This tricycle can be operated by physically challenged persons to travel to longer distances without much effort.